PENGAWASAN TERTIB LALU LINTAS OLEH SATLANTAS KOTA PEKANBARU (STUDI KASUS JALAN SUDIRMAN) - Tomi Kristian; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Traffic is the movement of vehicle activies and one of the media interaction that is vital on the life society, especially in areas of develovment and progress invarious fields of science and technology. It can we find in urban areas and especially in this study took place Pekanbaru (Case Study Sudirman Street) which is the center of Pekanbaru city and the center of all activity aspect of city life. The Rules Traffic Controlling done by Satlantas Pekanbaru not running optimally cause of still many cases of violations and traffic accident along with congestion occurs. The pupose of this study was to find out how the traffic controlling does by Satlantas Pekanbru (Case Study Sudirman Street) and to find out the factors that become inhibitor in Rules Traffic Controlling By Satlantas Pekanbaru City (Case Study Sudirman Street).The concept is the theory that researchers use Management And Management Controlling. This study used qualitative research methods to the assessment of descriptive data. In collecting the data, the researcher used interview techniques, observation, documentation and literature. By using key informants as a source of information and as a source of triangulation techniques in data validity.The results of this study indicate that the Rules Traffic Controlling By Satlantas Pekanbaru (Case Study Sudirman Street) is not maximized, because although decreased but still quite a lot of events and violations of traffic accidents each year, and for the officers there were irregularities to benefit personal. Factors that constrain the Rules Traffic Controlling By Satlantas Pekanbaru (Case Study Sudirman Street) is still a lack of personnel to supervise or the number of officers is not comparable to what was observed so that the task is less well done, as well as lack of awareness will drive the good and safe that can be expected to prevent the implementation of supervision can be seen from many riders who do not use safety equipment in driving and violating the warning signs.Keywords: Controlling, the Traffic Rules